2004
DOI: 10.1038/sj.onc.1207614
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon and TNFα cooperate with type II interferon for TRAIL induction and triggering of apoptosis in SK-N-MC EWING tumor cells

Abstract: Ewing's sarcoma is the second most common human bone tumor in childhood. Here, we investigated the sensitivity of the Ewing tumor cell line, SK-N-MC, to the apoptotic effect of type I (IFNa) and type II (IFNc) interferons and TNFa. We demonstrate that although IFNa and TNFa alone are unable to induce cell death, they act in synergy with IFNc to induce SK-N-MC cell apoptosis. The synergistic induction of apoptosis correlated with the synergistic induction of TNFa-related apoptosis-inducing ligand (TRAIL) mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
(52 reference statements)
1
15
0
Order By: Relevance
“…The increased expression of a death receptor ligand, either alone or accompanied by the increase in its receptor, has been previously shown to induce cell death in Ewing's sarcoma cells. Abadie et al (2004) reported that a combination of cytokines (TNF- α with interferon γ or interferon α with interferon γ ) induces cell death in SK-N-MC cells, and that this is mediated by the increased expression of TRAIL. A collaboration of TRAIL and interferon γ was also observed in vivo in a xenograft model of Ewing's sarcoma (Merchant et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of a death receptor ligand, either alone or accompanied by the increase in its receptor, has been previously shown to induce cell death in Ewing's sarcoma cells. Abadie et al (2004) reported that a combination of cytokines (TNF- α with interferon γ or interferon α with interferon γ ) induces cell death in SK-N-MC cells, and that this is mediated by the increased expression of TRAIL. A collaboration of TRAIL and interferon γ was also observed in vivo in a xenograft model of Ewing's sarcoma (Merchant et al , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of TRAIL gene expression and protein synthesis is known to occur in Ewing sarcoma, and thyroid carcinoma cell lines following intereferon (IFN)/cytokine treatment, contributing to apoptosis of the malignant cells in an autocrine and paracrine manner [10,11]. TRAIL serum levels in melanoma patients are found to be significantly elevated following IFN-α administration [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, further investigation of this pathway is underway. It has been shown that IFNs can induce expression of TRAIL [99], and recent studies have documented strong synergistic in vitro and in vivo antitumour effects when Type I IFN-α or -β are given with ifosfamide [100] or with Type II IFN-γ [101]. Furthermore, in these preclinical models, the antitumour effect correlates with TRAIL induction, which would suggest that TRAIL contributes to the triggering of apoptosis in ESFT cells in an autocrine or paracrine manner.…”
Section: Expert Opinion and Conclusionmentioning
confidence: 98%